2002
DOI: 10.1111/j.1745-9125.2002.tb00951.x
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering the Broken Homes/Delinquency Relationship and Exploring Its Mediating Mechanism(s)*

Abstract: As a result of methodological limitations, prior research may have artificially attenuated the magnitude of the broken homes/delinquency relationship. As a result of theoretical limitations, prior research has achieved only limited success in identifying the mechanism through which broken homes may promote delinquency. The present study addresses both issues using a national probability sample of 1, 725 adolescents. Results suggest that divorce/separation early in the life course may be more strongly related t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
117
1
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 101 publications
(123 citation statements)
references
References 53 publications
4
117
1
1
Order By: Relevance
“…Price and Kunz (2003) found in a meta-analysis of 72 studies that children from divorced homes have higher delinquency rates compared to children from intact homes. Heck and Walsh (2000) measured both delinquency and maltreatment more comprehensively and found that when controlling for family structure, the maltreatment to delinquency risk was significant, whereas Rebellon (2002) used a national probability sample of adolescents and identified that divorce experienced by younger children might be a stronger predictor of later delinquency than previous research had found.…”
Section: Family Structurementioning
confidence: 46%
See 3 more Smart Citations
“…Price and Kunz (2003) found in a meta-analysis of 72 studies that children from divorced homes have higher delinquency rates compared to children from intact homes. Heck and Walsh (2000) measured both delinquency and maltreatment more comprehensively and found that when controlling for family structure, the maltreatment to delinquency risk was significant, whereas Rebellon (2002) used a national probability sample of adolescents and identified that divorce experienced by younger children might be a stronger predictor of later delinquency than previous research had found.…”
Section: Family Structurementioning
confidence: 46%
“…For this sam ple of maltreated children, the only risk factor that was significantly related to later delinquency was whether their parents divorced-here this divorce outcome made later adjudication less likely for the youth when compared to youth from never-married families. This is somewhat surprising when reviewing more recent family functioning literature, which found higher delinquency rates for children and youth, with and without maltreatment histories, who experienced parental divorce (Heck & Walsh, 2000;Price & Kunz, 2003;Rebellon, 2002). These differential outcomes may be explained in that very limited research to date has tried to explain the maltreatment, delinquency, and family structure connections.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…Studies on family structure and age interaction with delinquency have shown that family structure effect the attachment between the child and his parents and relationship with deviant peers and also shown that the important of these factors change according to the age where it bad influence on the delinquents come more when it occurs is an early childhood (Kierkus&Bear, 2002;Rebellon, 2002). …”
Section: Introductionmentioning
confidence: 99%